PERBEDAAN LITERASI KEUANGAN DENGAN UJI KRUSKAL WALLIS PADA MAHASISWA EKONOMI - Mei Kristiani Harefa; Maria Widyastuti (Fakultas Ekonomi dan Bisnis, Universitas Wiraraja Madura, 2023)
The purpose of this study was to find out whether there are differences in financial literacy among students of the Faculty of Economics in Surabaya when viewed from factors: gender, age, generation, study program, GPA, place of residence, status, amount of income, amount of expenditure, account ownership and level of education. old. Understanding of financial literacy in terms of general knowledge, knowledge of insurance financial transactions, knowledge of saving and loan transactions and knowledge of investing. The population of this study were economics students studying in Surabaya, the distribution of the questionnaire via Google form and the sample that was successfully taken was 259 students. The test tool used to determine differences is using the Kruskal Wallis Test. The results of this study indicate that there are significant differences in understanding financial literacy in terms of the several factors studied.